2015
DOI: 10.1186/s12864-015-2117-9
|View full text |Cite
|
Sign up to set email alerts
|

Genome wide association and genomic prediction for growth traits in juvenile farmed Atlantic salmon using a high density SNP array

Abstract: BackgroundThe genetic architecture of complex traits in farmed animal populations is of interest from a scientific and practical perspective. The use of genetic markers to predict the genetic merit (breeding values) of individuals is commonplace in modern farm animal breeding schemes. Recently, high density SNP arrays have become available for Atlantic salmon, which facilitates genomic prediction and association studies using genome-wide markers and economically important traits. The aims of this study were (i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
203
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 215 publications
(234 citation statements)
references
References 36 publications
27
203
4
Order By: Relevance
“…While the initial concept of GS was to detect and utilise population-wide linkage disequilibrium between genome-wide markers and QTL (Meuwissen et al, 2001), the benefits of genomic selection also include a more accurate estimate of the genetic relationship between any two individuals than could be given by pedigree records alone, particularly within families . In all studies of aquaculture species to date, the use of GS has resulted in higher prediction accuracy of breeding values than the use of pedigree information alone (Odegård et al, 2014;Tsai et al, 2015;Dou et al, 2016). A prerequisite for genomic selection is a platform to generate high-density SNP marker genotypes across populations of animals and SNP arrays have been developed for several aquaculture species, including Atlantic salmon Yáñez et al, 2016), rainbow trout (Palti et al, 2015), common carp (Xu et al, 2014), and catfish .…”
Section: Current Methods Of Breeding For Disease Resistancementioning
confidence: 99%
“…While the initial concept of GS was to detect and utilise population-wide linkage disequilibrium between genome-wide markers and QTL (Meuwissen et al, 2001), the benefits of genomic selection also include a more accurate estimate of the genetic relationship between any two individuals than could be given by pedigree records alone, particularly within families . In all studies of aquaculture species to date, the use of GS has resulted in higher prediction accuracy of breeding values than the use of pedigree information alone (Odegård et al, 2014;Tsai et al, 2015;Dou et al, 2016). A prerequisite for genomic selection is a platform to generate high-density SNP marker genotypes across populations of animals and SNP arrays have been developed for several aquaculture species, including Atlantic salmon Yáñez et al, 2016), rainbow trout (Palti et al, 2015), common carp (Xu et al, 2014), and catfish .…”
Section: Current Methods Of Breeding For Disease Resistancementioning
confidence: 99%
“…Ssa11 was also found to contain growth QTL in the transAtlantic backcross families of Boulding et al (2008), and Pedersen et al (2013), and in previous studies using European salmon (Houston et al 2009;Gutierrez et al 2012;Besnier et al 2015). Ssa15 (Reid et al 2005;Gutierrez et al 2012), Ssa18 (Gutierrez et al 2012;Tsai et al 2015), and Ssa19 (Gutierrez et al 2012) have also previously been reported to contain growth QTLs.…”
Section: Length and Weightmentioning
confidence: 95%
“…All QTL were located relative to a physical map of the Atlantic salmon genome allowing putative candidate genes to be identified and our QTL to be compared with those found in future studies. Finer QTL mapping and genome-wide association study (Gutierrez et al 2015;Tsai et al 2015) will be necessary to see if the candidate genes proposed to underlie these traits continue to be associated with them in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These traits inluence the commercial value of farmed aquatic organisms. Traits for body weight and length have been identiied in several ish species such as Atlantic salmon [149], rainbow trout [150], Big heard carp (H. nobilis) [151], common carp [152,153] and tilapia (Oreochromis niloticus) [154], nine spined stickleback (Pungitius pungitius) [155] and Arctic char (Salvelinus alpinus) [156]. In shrimps and prawns, body weight and length traits have been identiied in kruma shrimp [157,158], Chinese shrimp [159], Giant fresh water prawn [160], Ridge white prawn [161] and Oriental river prawns [162].…”
Section: Growth Traitsmentioning
confidence: 99%